Conflicting Demands on the International Monetary Fund - Krueger, Anne O (American Economic Review, 2000)
In the wake of the Mexican, Asian, and other crises of recent years, calls for a “new international financial architecture” have been heard from many quarters. While other questions, such as the wisdom of the International Monetary Fund (IMF) practice of long-term support for low-income countries, have also been raised, the central issue is the role that the IMF should play in reducing the likelihood of crises and in handling them once they arise, and it is this issue that is addressed in this paper. Of the other important questions, only one needs to be mentioned here. That is, in recent years, the IMF has begun paying attention to issues such as poverty alleviation, income distribution, and other questions which are not only far away from its traditional competence, but which also detract seriously from its capacity to handle macroeconomic crises, where it has possessed competence. The IMF’s ability to deal satisfactorily with the central concerns discussed here will be significantly impaired if it continues to take on these other issues. Turning then to crisis management, many suggestions have been made for changes in the IMF role. These range from its abolition to large-scale expansion of IMF resources, with many others in between. Prescription should follow diagnosis. I start, therefore, with a diagnosis as to what happened in many of the crisis countries. On that basis, I argue that there are two distinct lines along which changes could be made, and that many of the apparently conflicting demands placed upon the IMF reflect either failure to diagnose the nature of the problem or an unwillingness to come to grips with the central dilemma. Thereafter, some of the proposals currently being aired are evaluated in light of the diagnosis. The key to understanding the issues surrounding crises of the type that occurred in East Asia in 1998 lies in the proposition that most, but not all (Brazil, for example, is an exception) of the “crisis countries” of recent years have really experienced two crises almost simultaneously. They have had a balance-of-payments crisis and a financial crisis. The balance-of-payments crisis has come about as countries have been unable to maintain their obligations to foreign creditors and their commitments to maintain an exchange-rate regime. Balance-of-payments crises are familiar from earlier years, when the IMF routinely supported stabilization programs. Two characteristics of these “traditional” crises should be noted. First, efforts to defend an exchange rate and a commitment to service foreign-currency-denominated debt have almost always been precipitating factors in balance-ofpayments crises, and the solution has almost always entailed adjustment of the nominal exchange rate, if not abandonment of a fixedexchange-rate regime and adoption of a floating exchange rate. Second, key economic policymakers in the crisis country and IMF staff typically had several months in which to work out adjustment programs. In the case of the highly publicized Mexican announcement of inability to maintain debt-servicing in August 1982, for example, an IMF program was not agreed upon until many months later. Financial crises, like balance-of-payments crises, have occurred frequently in the postWorld War II period. A financial crisis comes about when the banking system is threatened with insolvency. It can occur (as in Japan in the 1990’s and in Sweden in 1992) without a balance-of-payments crisis. It is usually centered in the banking system, although the United States savings-and-loan crisis demonstrated that it can arise elsewhere in the financial system. Generally, financial crises are characterized by a large proportion of nonperforming loans (recognized or otherwise) in a country’s banks or the insolvency of other key financial institutions. * Department of Economics, Landau Building, Stanford University, Stanford, CA 94305. I am indebted to Jeffrey Frankel, Nicholas Hope, and Aaron Tornell for helpful comments on an earlier draft of this paper.